Continuous positive airway pressure (CPAP) after lung resection: a randomized clinical trial - Roceto, Lígia dos Santos; Galhardo, Fernanda Diório Masi; Saad, Ivete Alonso Bredda; Toro, Ivan Felizardo Contrera (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Noninvasive mechanical ventilation during the postoperative period (PO) following lung resection can restore residual functional capacity, improve oxygenation and spare the inspiratory muscles. The objective of this study was to assess the efficacy of continuous positive airway pressure (CPAP) associated with physiotherapy, compared with physiotherapy alone after lung resection. DESIGN AND SETTING: Open randomized clinical trial conducted in the clinical hospital of Universidade Estadual de Campinas. METHOD: Sessions were held in the immediate postoperative period (POi) and on the first and second postoperative days (PO1 and PO2), and the patients were reassessed on the discharge day. CPAP was applied for two hours and the pressure adjustment was set between 7 and 8.5 cmH2O. The oxygenation index (OI), Borg scale, pain scale and presence of thoracic drains and air losses were evaluated. RESULTS: There was a significant increase in the OI in the CPAP group in the POi compared to the Chest Physiotherapy (CP) group, P = 0.024. In the CP group the OI was significantly lower on PO1 (P = 0,042), than CPAP group. The air losses were significantly greater in the CPAP group in the POi and on PO1 (P = 0.001, P = 0.028), but there was no significant difference between the groups on PO2 and PO3. There was a statistically significant difference between the groups regarding the Borg scale in the POi (P < 0.001), but there were no statistically significant differences between the groups regarding the pain score. CONCLUSION: CPAP after lung resection is safe and improves oxygenation, without increasing the air losses through the drains. CLINICAL TRIAL REGISTRATION: NCT01285648